The Development of Branding Building Indicators of Private Vocational Colleges in The Northeast - Chaikanarakkul, Chetphong; Duangchatom, Kritkanok; Ruangsuwan , Chayakan (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The creation of a brand that is suitable and effective, resonating with students, parents, and the community, is crucial for private vocational colleges. Such a brand, when distinguished in the minds of service recipients, leads to a strong and efficient identity, increasing its value. This, in turn, contributes to an elevation in the number of students, guiding them toward the development of quality education within the private vocational college. This research aims, to development of branding-building indicators and to test the goodness of fit of the structural relationship model of branding-building indicators of private vocational colleges in the Northeast with empirical data. Methodology: The research is divided into 2 phases. Phases 1 to development of branding building indicators. The key informants group consisted of 9 experts, a sample group of 490 administrators and teachers. A research instrument is an interview form and questionnaire, with reliability between 0.84-0.97, and discrimination power between 0.45-0.74. Statistics to analyze data by mean and standard deviation. Phase 2 is to test the goodness of fit of the structural relationship model of branding building indicators of private vocational colleges in the Northeast with the empirical data, by second-order confirmatory factor analysis. Results: 1. The indicators of the branding building of private vocational colleges in the Northeast comprised 6 factors and 44 indicators. They were divided into brand Identity with 6 indicators, Brand awareness with 11 indicators, Corporate culture with 6 indicators, Brand relationship with 5 indicators, Organization transformation with 10 indicators, and Internationalization with 6 indicators. 2. The goodness of fit of the structural relationship model of branding building indicators of private vocational colleges in the Northeast. They were in good shape with empirical data, with Chi-Square = 990.175, df = 788, P-Value = 0.000, and CMIN. /df. = 1.275, CFI = .979, GFI = 0.917, TLI= .976, AGFI= 0.900, RMSEA= 0.023, RMR= 0.028, NFI= 0.907, IFI= 0.980 and all components were significantly correlated at the 0.001 level. Conclusion: The results show that the comprehensive structure of branding building for private vocational colleges in the Northeast comprises six factors with a total of 44 indicators. The subsequent emphasis on evaluating the goodness of fit in the structural relationship model underscores the importance of assessing how well the proposed model aligns with actual outcomes, providing insights into the effectiveness of branding efforts in these educational institutions.